2008
DOI: 10.2807/ese.13.21.18877-en
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus transmission from a nurse to a patient, France, 2005

Abstract: Infection by the Hepatitis B virus (HBV), which is often asymptomatic at the acute phase, can progress to chronic liver disease, particularly when infection occurs early in life. Hepatitis B is mainly transmitted sexually or through blood or body fluids. Episodes of healthcare-associated transmission of HBV have been previously described [1-3]. Transmission of HBV results either from patient to patient through invasive healthcare procedures with improper disinfection of devices used between patient care or fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hepatitis B infection accounts annually for 1 million deaths worldwide from hepatocellular carcinoma and cirrhosis and liver failure [1,8,9]. Different studies have shown that medical staffs are at high risk for hepatitis B infection [9][10][11][12].There is still an ongoing discussion about the extent to which medical staff might be at risk of hepatitis B or source of hepatitis B infection [11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B infection accounts annually for 1 million deaths worldwide from hepatocellular carcinoma and cirrhosis and liver failure [1,8,9]. Different studies have shown that medical staffs are at high risk for hepatitis B infection [9][10][11][12].There is still an ongoing discussion about the extent to which medical staff might be at risk of hepatitis B or source of hepatitis B infection [11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%